The Influence of Service Marketing Mix and Competitiveness on Customer Loyalty through Brand Equity of Loading and Unloading Services for Non-Container Goods at PT Pelindo Banjarmasin - A. Rangga; Nuril Huda; Asmawatiy, Cici (PT FORMOSA CENDEKIA GLOBAL, 2024)
Customer loyalty is believed to be determined by Service Marketing Mix and Competitiveness. Service Marketing Mix variables such as Product, Price, Place, Promotion, People, Process, Physical Evidence and Competitiveness Variables. The aims of this research are (1) to analyze the influence of Service Marketing Mix and competitiveness on Brand Equity of non-container loading and unloading services at PT Pelindo (Persero) Banjarmasin, (2) to analyze the influence of Brand Equity on Customer loyalty of non-container loading and unloading services at PT Pelindo Banjarmasin, (3) analyzing the influence of Service Marketing Mix and competitiveness on Customer loyalty through Brand Equity of loading and unloading services for non-container goods at PT Pelindo (Persero) Banjarmasin. This research uses quantitative methods. The population in this research is all customers/users of PT Pelindo Banjarmasin`s non-container loading and unloading services. Determination of sampling in this study used purposive sampling with the Quota Sampling method so that the sample in this study amounted to 135 companies. Data was collected through questionnaires and analyzed using the SEM-PLS. The results of this research show that (1) Service Marketing Mix and predicted competitiveness have a positive effect on Brand Equity of loading and unloading services for non-container goods at PT Pelindo (Persero) Banjarmasin, (2) Predicted Brand Equity has a positive effect on Customer loyalty of loading and unloading services. non-container goods at PT Pelindo Banjarmasin, (3) Service Marketing Mix and predictable competitiveness loading and unloading services for non-container goods at PT Banjarmasin.